Planejamento e gestão urbanos e a implementação dos instrumentos do estatuto da cidade no município: o caso de Sabará - Corrêa, Sílvia Cristina (2016)
This work intends to analyze the limits of planning and urban management at the municipal level, from the case of Sabará, located in the metropolitan region of Belo Horizonte, taking considering the institutional constraints, financial, technical and administrative installed. From the above case, it sought to analyze how municipalities - especially mid-sized metropolitan - meet the principles, guidelines and, especially, the urban instruments provided for by Federal Law nº 10.257, knows as "The City Statute" and as has been facing difficulties political and institutional, financial, technical and administrative to implement and manage the planning and urban management. Ultimately, the analysis is extended to the current context of the Brazilian metropolitan areas in which the institutional and federal landmarks relating to urban policy raise questions and similar limiting factors to those addressed in the referenced municipality.